2017
DOI: 10.1177/1535370217731503
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D2 is a critical mediator of exercise-induced cardiac hypertrophy

Abstract: A number of signaling pathways underlying pathological cardiac hypertrophy have been identified. However, few studies have probed the functional significance of these signaling pathways in the context of exercise or physiological pathways. Exercise studies were performed on females from six different genetic mouse models that have been shown to exhibit alterations in pathological cardiac adaptation and hypertrophy. These include mice expressing constitutively active glycogen synthase kinase-3β (GSK-3βS9A), an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The increase in heart weight was mainly related to an increase in myocardial CSA. An increasing number of studies have shown that exercise can induce physiological hypertrophy of the heart [ 79 , 80 , 81 ]. Physiologically, hypertrophic hearts maintain or increase systolic function without cell death, while pathologically hypertrophic hearts are often accompanied by cardiomyocyte death, myocardial fibrosis, and systolic dysfunction, which will further progress to heart failure [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in heart weight was mainly related to an increase in myocardial CSA. An increasing number of studies have shown that exercise can induce physiological hypertrophy of the heart [ 79 , 80 , 81 ]. Physiologically, hypertrophic hearts maintain or increase systolic function without cell death, while pathologically hypertrophic hearts are often accompanied by cardiomyocyte death, myocardial fibrosis, and systolic dysfunction, which will further progress to heart failure [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used this early timepoint to investigate epicardial gene expression associated with cardiac remodeling. Voluntary wheel running has been shown to induce physiological cardiac hypertrophy, as measured by heart weight to body weight and cardiomyocyte cross-sectional area [35][36][37]. The DAVID analysis identified genes with significant changes in expression and grouped them into three major GO domains: biological process, cellular process, and molecular function.…”
Section: Microarray Analysismentioning
confidence: 99%
“…Soluble angiogenin binds endothelial cell surface receptors, is endocytosed, and then is trafficked to the nucleus where it participates in ribosomal RNA transcription to promote endothelial cell proliferation [42][43][44]. Nuclear translocation of angiogenin was shown to be required for VEGFstimulated angiogenesis [36,45].…”
Section: Differential Gene Expression Within Gene Ontologymentioning
confidence: 99%
“…Although it is not practical to measure exercise capacity in voluntary wheel-running rodents, growing evidence has shown that voluntary wheel running can significantly increase VO 2max in these rodents, although to a much less extent than treadmill running. 81 Unlike the intensity-dependent effects of treadmill running on physiological cardiac hypertrophy, voluntary wheel running for 3−4 weeks in mice 83 , 85 , 86 and 6−8 weeks in rats 87 , 88 , 89 , 90 can induce physiological cardiac hypertrophy. Voluntary wheel running-induced physiological cardiac hypertrophy shows different transcriptomic and metabolomic profiles compared to pathological hypertrophy.…”
Section: Animal-exercise Models Used In Cardiovascular Researchmentioning
confidence: 99%